2002
DOI: 10.1029/2001jd000323
|View full text |Cite
|
Sign up to set email alerts
|

Deep convection as a source of new particles in the midlatitude upper troposphere

Abstract: [1] A case study of new particle formation in the region downwind of a mesoscale convective system stretching across much of the central United States is presented. Airborne measurements were made of condensation nuclei (CN), cloud particle surface area, water vapor, and other gases. CN concentrations were greatly enhanced above and downwind of the cirrus anvil, with maximum concentrations of 45,000 per standard cm 3 . Volatility and electron microscope measurements indicated that most of the particles were li… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

15
114
3
1

Year Published

2008
2008
2021
2021

Publication Types

Select...
5
1
1

Relationship

1
6

Authors

Journals

citations
Cited by 120 publications
(138 citation statements)
references
References 53 publications
(70 reference statements)
15
114
3
1
Order By: Relevance
“…Because of low surface areas and low temperatures, nucleation can easily take place, but with the limited supply of aerosol precursors in this region, nucleation becomes sensitive to the extent of vertical motion. Our observations are inline with numerous observations (de Reus et al, 1998;Nyeki et al, 1999;Ström et al, 1999;Twohy et al, 2002;Lee et al, 2003;Minikin et al, 2003;Hermann et al, 2003;Carslaw and Kärcher, 2006) in which NPF was of- ten attributed to air mixing and convection. However, there were also some NPF cases where vertical motion clearly did not occur (<50% of the NPF cases), similarly to Young et al (2007), suggesting that airmass history is an important but not the only governing factor for aerosol nucleation in this region.…”
Section: Discussionsupporting
confidence: 78%
See 3 more Smart Citations
“…Because of low surface areas and low temperatures, nucleation can easily take place, but with the limited supply of aerosol precursors in this region, nucleation becomes sensitive to the extent of vertical motion. Our observations are inline with numerous observations (de Reus et al, 1998;Nyeki et al, 1999;Ström et al, 1999;Twohy et al, 2002;Lee et al, 2003;Minikin et al, 2003;Hermann et al, 2003;Carslaw and Kärcher, 2006) in which NPF was of- ten attributed to air mixing and convection. However, there were also some NPF cases where vertical motion clearly did not occur (<50% of the NPF cases), similarly to Young et al (2007), suggesting that airmass history is an important but not the only governing factor for aerosol nucleation in this region.…”
Section: Discussionsupporting
confidence: 78%
“…Hermann et al (2003) have provided so far the most comprehensive statistical analysis of NPF in the Northern Hemisphere tropopause region from three-year aircraft measurements; elevated particle number concentrations of 1500-8000 cm −3 were frequently observed in a wide range of latitudes (5 • N-50 • N). Twohy et al (2002) showed especially high number concentrations of new particles up to 45 000 cm −3 in the midlatitudes, associated with deep convection. Minikin et al (2003)'s aircraft studies showed relatively high concentrations of Aitken mode particles (up to 1000 cm −3 ) even in the Southern Hemisphere, where the anthropogenic emission of SO 2 is much lower than in the Northern Hemisphere; their comparison of particle number concentrations in the Northern and Southern Hemisphere indicates that new particles are directly related to aerosol precursor sources.…”
Section: Introductionmentioning
confidence: 99%
See 2 more Smart Citations
“…Heald et al (2005) proposed that the large and maintained source of OA particles is related to secondary aerosol formation from volatile organic compounds from either natural or anthropogenic sources transported from the ML. These observations are in agreement with studies showing that air masses transported from the ML can favour new particle formation in the FT (Twohy et al, 2002;Rose et al, 2015). Henne et al (2004) described events where long-range transported anthropogenic emissions have been identified on the Jungfraujoch research station, as well as events where slope winds contribute to the transportation of urban emissions from the ML into the FT.…”
Section: Introductionsupporting
confidence: 81%